Effect of mibefradil on CYP3A4 in vivo - Veronese, Maria L; Gillen, Lisa P; Dorval, Ellen P; Hauck, Walter W; Waldman, Scott A; Greenberg, Howard E (Journal of clinical pharmacology, 2003)
Mibefradil, a calcium channel blocker, was removed from the market because of adverse drug interactions with coadministered CYP3A4 substrates. This study examined the effect of mibefradil on the activity of hepatic and intestinal CYP3A4 in vivo, employing the erythromycin breath test (EBT) and oral midazolam pharmacokinetics. This was a two-period, single-blind, placebo-controlled crossover study in which 8 male volunteers were randomized to the order of receiving placebo and a single 100-mg oral dose of mibefradil. Oral midazolam was coadministered with intravenous [14C N-methyl] erythromycin 1 hour after mibefradil/placebo administration. The EBT was performed 20 minutes following erythromycin administration. Blood and urine were collected during the 36 hours following probe drug administration for analysis of midazolam pharmacokinetics. Coadministration of mibefradil increased the Cmax of midazolam 3-fold, the AUC 8- to 9-fold, and the t1/2 4-fold. Mibefradil coadministration decreased the amount of exhaled 14CO2 in 6 of 8 subjects, with a mean decrease of 25%. It was concluded that a single oral dose of mibefradil significantly inhibits CYP3A4 in intestine and liver. These data support that adverse drug interactions involving mibefradil reflect inhibition of CYP3A4 in intestine and liver. Also, they suggest that the EBT, while a valid probe of in vivo hepatic CYP3A4 activity, is a single time point measurement and may be less sensitive than oral midazolam pharmacokinetics in detecting CYP3A4 inhibition.